Adipose tissue n-3 fatty acids and metabolic syndrome - Cespedes, Elizabeth (Eur J Clin Nutr, 2014)
BACKGROUND: Evidence regarding the relationship of n-3 fatty acids (FA) to type 2 diabetes (T2D) and metabolic syndrome components (MetS) is inconsistent. OBJECTIVE: To examine associations of adipose tissue n-3 FA with MetS. DESIGN: We studied 1611 participants without prior history of diabetes or heart disease who were participants in a population-based case-control study of diet and heart disease (The Costa Rica Heart Study). We calculated prevalence ratios (PR) and 95% confidence intervals (CI) for MetS by quartile of n-3 FA in adipose tissue derived mainly from plants [α-Linolenic acid (ALA)], fish [eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA)], or metabolism [docosapentaenoic acid (DPA), as well as the EPA:ALA ratio, a surrogate marker of delta-6 desaturase activity]. RESULTS: N-3 FA levels in adipose tissue were associated with MetS prevalence in opposite directions. The PR (95% CI) for the highest compared to the lowest quartile adjusted for age, sex, BMI, residence, lifestyle, diet and other fatty acids were 0.60 (0.44, 0.81) for ALA, 1.43 (1.12, 1.82) for EPA, 1.63 (1.22, 2.18) for DPA, and 1.47 (1.14, 1.88) for EPA:ALA, all p for trend <0.05. Although these associations were no longer significant (except DPA) after adjustment for BMI, ALA and DPA were associated with lower glucose and higher triglyceride levels, p<0.05 (respectively). CONCLUSIONS: These results suggest that ALA could exert a modest protective benefit, while EPA and DHA are not implicated in MetS. The positive associations for DPA and MetS could reflect higher delta-6 desaturase activity caused by increased adiposity.